IDENTIFIKASI JAMUR ANTAGONIS ASAL MEDIA LIMBAH JAMUR MERANG DAN POTENSINYA DALAM MENEKAN Rhizctonia solani PENYEBAB PENYAKIT PENYAKIT HAWAR PELEPAH PADI (Oryza sativa L.) - Ahmad Daffa Miftahussurur; Satriyo Restu Adhi; Sugiarto Sugiarto (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
One of the main diseases of rice is sheath blight caused by the fungus Rhizoctonia solani. The aim of this research is to isolate fungi originating from straw mushroom media waste which have antagonistic properties to the fungus R. solani. The research was carried out at the Biotechnology Laboratory, Faculty of Agriculture, Singaperbangsa University Karawang. The stages of this research consisted of: (1) isolation and identification of antagonist fungi from straw mushroom media waste, (2) in-vitro antagonism test using a Completely Randomized Design (CRD) repeated three times, (3) pathogenicity test of antagonist fungi on germination rice seeds. From the experimental results, 9 isolates of antagonistic fungi were obtained, 7 fungal genera were identified, consisting of 4 genera Trichoderma sp. and 3 genera Aspergillus sp. Based on the AUCGC results and the percentage of inhibition, the results show that several fungi from straw mushroom media waste have the ability to antagonize and inhibit R. solani. Treatment of JMA2 (Trichoderma sp.) and R. solani in the antagonism test gave the smallest AUCGC value of 29.38 and the largest inhibition percentage of up to 31.22%.